2014
DOI: 10.2478/s11756-014-0371-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive effect of bilberry (Vaccinium myrtillus) against cisplatin-induced oxidative stress and DNA damage as shown by the comet assay in peripheral blood of rats

Abstract: The aim of this study was to evaluate the chemopreventive effect of bilberry on cisplatin induced oxidative stress and DNA damage in rat blood. Twenty-one female Wistar-Albino rats were divided into three groups: group Iuntreated; group II -treated with cisplatin (single dose 7.5 mg/kg b.w.); and group III -treated with cisplatin (single dose 7.5 mg/kg b.w.) and bilberry (200 mg/kg b.w. for 10 days). Antioxidant enzyme systems including superoxide dismutase, catalase, glutathione peroxidase and the level of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
(49 reference statements)
0
5
0
1
Order By: Relevance
“…It is reported that against cisplatin-induced oxidative stres and DNA damage consumption of 200 mg/kg bilberry for 10 days, effective on antioxidant enzyme systems and MDA level and significantly decrease the comets. These results show that bilberry is capable of preventing genotoxic and cytotoxic damage caused by cisplatin in peripheral blood cells in rats [34]. V. myrtillus extract has been reported to have cytoprotective effect in various models in vivo.…”
Section: Discussionmentioning
confidence: 54%
“…It is reported that against cisplatin-induced oxidative stres and DNA damage consumption of 200 mg/kg bilberry for 10 days, effective on antioxidant enzyme systems and MDA level and significantly decrease the comets. These results show that bilberry is capable of preventing genotoxic and cytotoxic damage caused by cisplatin in peripheral blood cells in rats [34]. V. myrtillus extract has been reported to have cytoprotective effect in various models in vivo.…”
Section: Discussionmentioning
confidence: 54%
“…Today, substances of plant origin are considered as one of the most promising sources of beneficial, physiologically active metabolites. The fruits of V. myrtillus are well known due to their abundance in health-promoting biologically active compounds and are very popular in different regions of the world as herbal medicinal products [1,2,[6][7][8][9][10]. On the other hand, although several reports are available about the promising biological properties and presence of many active phytochemicals in VM leaves and stems.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, they are rich in anthocyanins, which in recent years have drawn study interest due to their wide range of uses. There is a vast amount of literature data mentioning the antioxidant, genoprotective, anticancer, cardioprotective, anti-inflammatory, ocular, neuroprotective and antimicrobial effects of this plant [2,[6][7][8][9][10]. Bilberries are also good sources of different vitamins, macroand micronutrients as well as phenolic compounds and carotenoids.…”
Section: Introductionmentioning
confidence: 99%
“…Additional-ly, CP has been found to reduce the activity of antioxidants like superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), and glutathione S-transferase (GST), which represent a defense system against free radical damage [6,7]. Oxidative stress can lead to alterations in protein synthesis and inhibit DNA transcription and replication [8]. Another proposed mechanism of CP-induced toxicity in the testes is its ability to induce apoptosis in germ cells [9].…”
Section: Introductionmentioning
confidence: 99%